TRANSLATED WORKS IN LATIN IN THE TRANSLATION CENTERS OF MEDIEVAL SPAIN (Part I: books on exact Sciences). (Scientific journal of the Fergana State University, 2023)
The article provides information about translations into Latin of about 60 works of scientists of antiquity and the medieval East, made in the translation centers of Spain. It analyzes and classifies the information collected from the scientific literature on the history of translations in Spain in the XII–XIII centuries.